Cheminformatics of Natural Products. Volume 1, - Ntie-Kang, Fidele (De Gruyter, 2020)
Vol. 1 of Chemoinformatics of Natural Products presents an overview of natural products chemistry, discussing the chemical space of naturally occurring compounds, followed by an overview of computational methods.- Resumé vydavatel
Keywords: chemoinformatika; přírodní látky; cheminformatics; natural products; elektronické knihy; monografie; electronic books; monographs